Development of Road Damage Report Application (Road Repair) - Ramli, Ahmad Izzuddin; Saringat, Mohd Zainuri (Applied Information Technology And Computer Science, 2022)
Road maintenance is essential to establish a safe and sound road for citizens to use in their daily life. Due to the frequently used and natural causes like water flow or flood, there will be some damages occur which need the care from the road authority. Unfortunately, only a few are willing to spare their time in lodging the damaged road report as it is time-consuming. All smartphones have a Global Positioning System sensor which will be used to determine the exact location of the problematic zone for this application. The camera can be utilized to capture the damaged road visual proof. The system generates a form consisting of all data entered by the user along with the location and visual proof and sends that to the central server notifying the concerned authority. Thus, helping citizens to easily lodge the damaged road complaint.